South Korea: business associations and the South Korean 'miracle'. - FLAKE, L. Gordon (1995)
Notes that while various aspects of South Korea's development process have come under close scrutiny by those hoping to learn from the country's experience, one aspect that has escaped significant attention is the role of its business associations. Discusses the relationship between government and business in South Korea.